SPECT/CT Scan Images to Evaluate COVID-19 Pulmonary Complications: A Systematic Review - Coelho-Oliveira, Ana Carolina; Taiar, Redha; Jaques-Albuquerque, Luelia Teles; Valério-Penha, Ana Gabriellie; Reis-Silva, Aline; Ferreira-Souza, Luiz Felipe; da Cunha de Sá-Caputo, Danúbia; Bernardo-Filho, Mario (International Journal of Environmental Research and Public Health, 2025)
Introduction: The highly contagious 2019 novel coronavirus that causes coronavirus disease 2019 increased the scientific community’s interest in diagnosing and monitoring COVID-19. Due to the findings about the association between COVID-19 infection and pulmonary disturbances, the need for the use of complementary tests that can be carried out, preserving the health of patients, has grown. In this context, single-photon emission computed tomography (SPECT) was performed during the COVID-19 pandemic to assess and try to diagnose lung lesions. The aim of this current review was to investigate the types of SPECT images most commonly used and the main pulmonary parenchymal lesions and different lung perfusion abnormalities observed in these images in individuals with COVID-19 in different countries in the world. Materials and Methods: Electronic searches in the MEDLINE/PubMed, Embase, Scopus, Web of Science, and CINAHL databases were conducted in December 2022. Studies that used SPECT/CT scans to evaluate pulmonary involvements due to COVID-19, with no language restriction, were included. Two reviewers, who independently examined titles and abstracts, identified records through the database search and reference screening, and irrelevant studies were excluded based on the eligibility criteria. Relevant complete texts were analyzed for eligibility, and all relevant studies were included in a systematic review. Results: Eight studies with regular methodological quality were included. The types of SPECT examinations used in the included articles were SPECT/CT, Q SPECT/CT, and V/Q SPECT. The possible pulmonary complication most observed was pulmonary embolism. Conclusions: This systematic review demonstrated that SPECT/CT scans, mainly with perfusion methods, allow the maximum extraction of benefits from pulmonary images, in safety, suggesting efficiency in the differential diagnosis, including of respiratory diseases of different etiology, and with diagnostics and additional analyses, can possibly aid the development of suitable therapeutic strategies for each patient. Randomized clinical trials and studies of good methodological quality are necessary to confirm the findings of this review and help better understand the types of SPECT images most commonly used and the main pulmonary parenchymal lesions observed in the images in individuals with COVID-19.
Number: 2
Keywords: SPECT images; coronavirus; lung abnormalities; lung perfusion; single positron emission tomography